Institutional convergence in Europe - Nina Schönfelder; Helmut Wagner (Kiel Institute for the World Economy (IfW), 2018)
This paper applies the statistical concepts of σ-convergence and unconditional β-convergence to institutional development within several country groups hierarchized to the degree of European integration (e.g., euro area). Two sets of indicators are employed to measure institutional development: first, the Worldwide Governance Indicators, and second, the product market regulation indicator of the OECD and the Doing Business distance to frontier indicator of the World Bank. The authors can clearly confirm institutional β-convergence within the EU and its aspirants, which is mainly driven by the new Member States and acceding, candidate, and potential candidate countries. However, euro-area countries converge only in the area of product market and business regulation- not in the area of governance. In fact, the authors show evidence for β-divergence in rule of law within the first twelve euro-area members. Concerning σ-convergence, the results are less clear. Only the EU including the EU aspirants reduced the cross-country variance in all aspects of institutional development.
Keywords: E02; K20; L50; 330; institutional convergence; governance; product market regulation; business regulation; European integration